The translated city (translation. a transdisciplinary journal, 2021)
To think of the modern city- Cairo, London, Istanbul, Lagos, or Buenos Aires-is to experience a perpetual translating machine. Economical, cultural, and historical forces are here locally configured and acquire form, substance, and sense. These days much attention is given to how global flows become local realities in the multiple realisations of 'globalisation; but the archive that the city proposes actually represents an altogether deeper set of sedimentations. Cities as the sites of cultural encounters-from fifth century Athens with its Greeks, Persians, and Egyptians, to present- day, multi-cultured Los Angelesare precisely where the outside world pushes into our interiors to propose immediate proximities.